Earnings gaps, Segmentation and Competitiveness in the Ghanaian Labour Market - Nana C. Nimoh; Abdilahi Ali; Tony Syme (Salford Business School, 2020)
This paper examines the labour market dynamics of Ghana by specifically assessing: (1) the informal-formal earnings gaps in the country, and (2) whether informal sector employment is due to labour market segmentation (i.e. last resort) or comparative advantage (voluntary). Our findings indicate that there are significant formal/informal earnings gaps in the Ghanaian labour market which is robust to industry and regional differences. Interestingly, we find that, even though males suffer earnings penalties within the informal sector, the penalty is much higher for females. Additionally, the study identifies the existence of two distinct segments within the informal labour market, each characterised by a different earnings profile. Thus, there is both segmentation and competitiveness within the informal labour market. Our results highlight the importance of designing appropriate policies that can tackle both voluntary and involuntary informal sector employment.
Keywords: J46; O17; C14; N17; 330; Informal labour market; finite mixture model; segmentation; comparative advantage; Ghana